2021
DOI: 10.1021/acs.joc.1c01639
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Modular Hybrid Strategy for the Diversity-Oriented Synthesis of Lamellarins/Azalamellarins with Anticancer Cytotoxicity

Abstract: A modular hybrid strategy has been developed for the diversity-oriented synthesis of lamellarins/azalamellarins. The common pentacyclic pyrrolodihydroisoquinoline lactone/lactam core was formed via the Michael addition/ring closure (Mi-RC) and the copper­(I) thiophene-2-carboxylate (CuTC)-catalyzed C–O/C–N Ullmann coupling. Subsequent direct functionalization at C1, DDQ-mediated C5C6 oxidation, and global deprotection of all benzyl-type O- and N-protecting groups furnished the desired lamellarins/azalamellari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The NaHCO 3 ‐mediated Grob coupling of 1‐methylisoquinoline 11 and 3‐nitrocoumarin 17 (prepared from condensation of 2‐hydroxy‐4‐methoxybenzaldehyde with ethyl nitroacetate) [17] in a sealed tube gave the lamellarin pentacyclic core 18 in 30% yield [5c] . Bromination of 18 by NBS in THF at room temperature for 1 h furnished the brominated pentacycle 19 in 85% yield [18] . The Suzuki coupling [19] of 19 with (4‐methoxyphenyl)boronic acid in DME yielded the protected lamellarin 20 in 83% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NaHCO 3 ‐mediated Grob coupling of 1‐methylisoquinoline 11 and 3‐nitrocoumarin 17 (prepared from condensation of 2‐hydroxy‐4‐methoxybenzaldehyde with ethyl nitroacetate) [17] in a sealed tube gave the lamellarin pentacyclic core 18 in 30% yield [5c] . Bromination of 18 by NBS in THF at room temperature for 1 h furnished the brominated pentacycle 19 in 85% yield [18] . The Suzuki coupling [19] of 19 with (4‐methoxyphenyl)boronic acid in DME yielded the protected lamellarin 20 in 83% yield.…”
Section: Resultsmentioning
confidence: 99%
“…[5c] Bromination of 18 by NBS in THF at room temperature for 1 h furnished the brominated pentacycle 19 in 85% yield. [18] The Suzuki coupling [19] of 19 with (4methoxyphenyl)boronic acid in DME yielded the protected lamellarin 20 in 83% yield. Final exhaustive demethylation of 20 with excess of BBr 3 afforded the tridemethoxy lamellarin D ( 16) in 81% yield.…”
Section: Resultsmentioning
confidence: 99%
“…5,18 The unbridled key goal is, besides appropriate strategies to synthetically approach these natural compounds, 17,[19][20][21] to create new analogues as innovative drug-like compounds with potent antitumor activities. [22][23][24] Zheng et al reported synthesis and investigation of novel glycosylated lamellarin D compounds wherein glycosyl moieties improve important physicochemical properties of active compounds, especially the solubility in water. 25 Another study revealed A-ring modied lamellarin N analogues as potent noncovalent inhibitors of EGFR T790M/ L858R mutant, which is responsible for non-small cell lung cancer resistance.…”
Section: Introductionmentioning
confidence: 99%
“… Of note, after Lamellarin was initially isolated from marine prosobranch mollusk, more than 70 examples of such skeletons have been found up to date, and scientists worldwide have been devoted to investigating their synthetic methodologies and drug properties . In general, there were two common strategies to synthesize such fused [6/6/5] heterocycles: (a) the formation of N-alkylation ylides of isoquinoline and reaction with various inter- or intramolecular unsaturated π-bonds and (b) pyrrole functional group stitching to synthesize Lamellarin scaffolds . Although straightforward and meaningful, both methods suffer from the preinstallation of multifunctional groups, low efficiency of long-step transformation, and harsh conditions often needed.…”
Section: Introductionmentioning
confidence: 99%